A history of modern Jewish religious philosophy. - Schweid, Eliezer. (Supplements to The Journal of Jewish Thought and Philosophy, 2015)
The culmination of Eliezer Schweid's life-work as a Jewish intellectual historian, this five-volume work provides a comprehensive, interdisciplinary account of the major thinkers and movements in modern Jewish thought, in the context of general philosophy and Jewish social-political historical developments, with extensive primary source excerpts. Volume Two, \'The Birth of the Jewish Historical Studies and the Modern Jewish Religious Movements,\' discusses the major Jewish thinkers of central and eastern Europe before 1881, in connection with the movements they fostered: German-Jewish Wissenschaft (Zunz), Reform (Formstecher, Samuel Hirsch, Geiger), Neo-Orthodoxy (S. D. Luzzatto, Steinheim, Samson Raphael Hirsch), Positive-Historical (Frankel, Graetz), and Neo-Haredi (Kalischer, Malbim, Hayyim Volozhiner, Salanter). In addition, extensive attention is given to the thinkers of the east-European Haskalah, both earlier (Levinsohn, Rubin, Schorr, Mieses, Abraham Krochmal) and later proto-Zionist thinkers (Zweifel, Smolenskin, Pines, Lilienblum).